До питання навчання іншомовному професійно орієнтованому спілкуванню в аграрному виші - Піддубцева, Ольга Ігорівна; Piddubtseva, Olga (ХНУ імені В.Н. Каразіна, 2019)
В статті вивчено особливості навчання іншомовному професійно орієнтованому спілкуванню в аграрному виші. Peculiarities of teaching foreign-language professional-oriented communication in agrarian institute of higher education are studied in the article.
To the problem of teaching foreign language professional-oriented communication in agrarian institute of higher education
Keywords: навчання; teaching; іноземна мова; foreign language; аграрний виш; agrarian institute of higher education